Doping effect of zeolite-templated carbon on electrical conductance and supercapacitance properties. (30th June 2022) - Choi, Woosuk; Bera, Raj Kumar; Han, Seung Won; Park, Hongjun; Go, Tae Won; Choi, Minkee; Ryoo, Ryong; Park, Jeong Young
Abstract: The atomic doping of microporous carbon can give rise to variations in material properties and has been used to enhance electrochemical and charge storage properties. Here, we have investigated the effect of doping of nitrogen (N) and sulfur (S) on zeolite-templated carbon (ZTC). N-doped zeolite-templated carbon (N-ZTC) with various structures, including pyridinic N, pyrrolic N, and graphitic N, has a different composition ratio depending on the temperature at which it was synthesized. The composition, electrical conductance, and work functions of doped ZTC were investigated with X-ray photoelectron spectroscopy (XPS), conductive atomic force microscopy (C-AFM), and Kelvin probe force microscopy (KPFM), respectively. We found that N-doped ZTC synthesized at the highest temperature (700 °C) showed the highest graphitic N ratio and electrical conductance, indicating an optimized n-type doping effect. On the other hand, N-ZTC synthesized at the lowest temperature (500 °C) showed a high ratio of pyridinic N and pyrrolic N and low electrical conductance. These doped ZTCs were tested as supercapacitor electrode materials and exhibited low ohmic drop and high capacitance, with an increase in the conductance of the doped ZTCs samples. The structure of graphitic N showed an n-type doping effect in ZTC, whereas pyridinic N showed a weak n-type doping effect. This phenomenon was explained by measuring the work function of KPFM. The results suggest a direct relationship between electrical conductance and carbon-dopant bonding in doped microporous structures, suggesting the possibility of tuning material properties with atomic doping. Graphical abstract: Image 1